Bottom-up analysis using liquid chromatography–Fourier transform mass spectrometry to characterize fucosylated chondroitin sulfates from sea cucumbers. (30th July 2019) - Yan, Lufeng; Li, Lingyun; Li, Junhui; Yu, Yanlei; Liu, Xinyue; Ye, Xingqian; Linhardt, Robert J; Chen, Shiguo
Abstract: Fucosylated chondroitin sulfates (FCSs) from sea cucumbers have repetitive structures that exhibit minor structural differences based on the organism from which they are recovered. A detailed characterization of FCSs and their derivatives is important to establish their structure–activity relationship in the development of new anticoagulant drugs. In the current study, online hydrophilic interaction chromatography–Fourier transform mass spectrometry (FTMS) was applied to analyze the FCS oligosaccharides generated by selective degradation from four species of sea cucumbers, Isostichopus badionotus, Pearsonothuria graeffei, Holothuria mexicana and Acaudina molpadioides . These depolymerized FCS fragments were quantified and compared using the glycomics software package, GlycReSoft. The quantified fragments mainly had trisaccharide-repeating compositions and showed significant differences in fucosylation (including its sulfation) among different species of sea cucumbers. Detailed analysis of FTMS ion peaks and top-down nuclear magnetic resonance spectroscopy of native FCS polysaccharides verified the accuracy of this method. Thus, a new structural model for FCS chains from these different sea cucumbers was defined. This bottom-up approach provides rich detailed structural analysis and provides quantitative information with high accuracy and reproducibility and should be suitable for the quality control in FCSs as well as their oligosaccharides.